SIKAP DALAM MENGHADAPI KEMATIAN MENURUT AJARAN BUDDHA THERAVADA - Nur Fitriyana; Puji Riani (JIA (Jurnal Ilmu Agama), 2019)
Death is something that is sure to happen to every creature. Everyone has a different reaction to facing death. Some may be afraid, others may become anxious, the rest accept it with a strong heart. In Buddhism, a person's attitude in the face of death is also taught, and also how to act against people who are facing death. Theravada Buddhism teaches how to prepare for death for yourself and how to calm people who are facing death by reciting the names of the Buddha